2008
DOI: 10.1113/expphysiol.2007.041442
|View full text |Cite
|
Sign up to set email alerts
|

Brief femoral artery ischaemia provides protection against myocardial ischaemia–reperfusion injury in rats: the possible mechanisms

Abstract: The present study was conducted to examine the role of nitric oxide (NO), mitochondrial ATP-sensitive K + channels (mito K + ATP channels) and reactive oxygen species (ROS) and their interdependence in brief femoral artery ischaemia-induced myocardial preconditioning. To assess myocardial injury, myocardial infarction was induced by occlusion followed by reperfusion of the left anterior descending (LAD) coronary artery in anaesthetized rats and was assessed by triphenyl tetrazolium chloride (TTC) staining. Lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 55 publications
1
27
0
1
Order By: Relevance
“…Similarly, in rabbits preconditioned by pulmonary ischaemia, the NOS inhibitor L-NAME did not affect cardioprotection (Tang et al, 2014). However, in rats with brief femoral artery ischaemia-induced myocardial PC, cardioprotection was mediated by a combination of increased NO synthesis, opening of mitoKATP channels and increased ROS production (Shahid et al, 2008). In a rabbit renal ischaemia-induced remote PC, cardioprotection was associated with a PPARmediated increase in iNOS expression (Lotz et al, 2011).…”
Section: Endogenous No In Remote Conditioningmentioning
confidence: 95%
“…Similarly, in rabbits preconditioned by pulmonary ischaemia, the NOS inhibitor L-NAME did not affect cardioprotection (Tang et al, 2014). However, in rats with brief femoral artery ischaemia-induced myocardial PC, cardioprotection was mediated by a combination of increased NO synthesis, opening of mitoKATP channels and increased ROS production (Shahid et al, 2008). In a rabbit renal ischaemia-induced remote PC, cardioprotection was associated with a PPARmediated increase in iNOS expression (Lotz et al, 2011).…”
Section: Endogenous No In Remote Conditioningmentioning
confidence: 95%
“…At least three hypotheses have been proposed to explain the occurrence of remote ischemic preconditioning reperfusion of an organ provokes a systemic protective response, which suppresses inflammation and apoptosis [82]. A role for ROS signaling in the remote organ and a reduction of redox stress in the target organ has been also proposed [93,194]. In particular, it appears that remote ischemic preconditioning is triggered by a combination of increased NO • synthesis, opening of mK ATP channels and increased ROS production in remote tissue.…”
Section: Remote Preconditioning a Brief Synopsismentioning
confidence: 99%
“…In particular, it appears that remote ischemic preconditioning is triggered by a combination of increased NO • synthesis, opening of mK ATP channels and increased ROS production in remote tissue. Moreover, it seems that NO • is working upstream and acts via activation of mK ATP channels, which subsequently increases the production of ROS [93,194]. Of note, it has been suggested that in man the activation of a single cell surface receptor may be sufficient to trigger preconditioning, while blockade of multiple pathways may be required to abolish the protective effect of remote preconditioning [156].…”
Section: Remote Preconditioning a Brief Synopsismentioning
confidence: 99%
“…Interestingly, production of NO, via activation of NO synthase, is seemingly not required for production of the cardioprotective factor, but is required for induction of the protective phenotype 54.…”
Section: Ric: History and Evolutionmentioning
confidence: 99%